The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s12119-019-09621-7
|View full text |Cite
|
Sign up to set email alerts
|

Living Outside Protocol: Polyamorous Orientations, Bodies, and Queer Temporalities

Abstract: This study investigates experiences of polyamory in a society where monogamy is the norm. Polyamory is when more than two people are involved in an intimate and/ or sexual relationship. The relationships are known to those involved, and everyone has the opportunity to have multiple relationships at the same time. In-depth interviews were completed with 22 persons in Sweden who identify as polyamorous. Drawing on Ahmed's phenomenological concepts of turning points and lines and Halberstam's concept of queer tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Queer relationships can also challenge relationship normativity (Barker, 2019;Carlström & Andersson, 2019;Lamont, 2017;Pallotta-Chiarolli et al, 2020;Sheff, 2013Sheff, , 2020. Building on the history of romantic friendships, LGBTQIA+ identities, and families of choice are newer understandings of how to queer relationships (the verb).…”
Section: Relationship Anarchy and Solo Polyamorymentioning
confidence: 99%
“…Queer relationships can also challenge relationship normativity (Barker, 2019;Carlström & Andersson, 2019;Lamont, 2017;Pallotta-Chiarolli et al, 2020;Sheff, 2013Sheff, , 2020. Building on the history of romantic friendships, LGBTQIA+ identities, and families of choice are newer understandings of how to queer relationships (the verb).…”
Section: Relationship Anarchy and Solo Polyamorymentioning
confidence: 99%
“…According to some authors, one of the consequences of mononormativity is that polyamory lacks a clear interactional framework guiding narratives of the self and relational commitments (Domínguez et al, 2017) since it exists outside of normatively structured everyday reality (Carlström, & Andersson, 2019). There is no single way to be polyamorous; therefore, polyamory has been described as a personal identity, a sexual orientation, a relationship structure, and a relational orientation (Jordan et al, 2017).…”
Section: Polyamory As a Liminal Objectmentioning
confidence: 99%
“…Bergström et al, 2013;Khaja et al, 2010) but has been identified in several sexuality related fields. For example, in a Swedish context such an approach has been reported in relation to LBGT groups (Björkman & Malterud, 2009), persons with experience of selling sex (Holmström, 2015;Larsdotter et al, 2011), and people with polyamorous lifestyles (Carlström & Andersson, 2019). Ultimately it may lead to suboptimal outcomes of the health encounter.…”
Section: Implications For Practicementioning
confidence: 99%